Crack Patterns Analysis on Structural Beam with Slag Cement. Issue 1 (June 2020) - Karolina, Rahmi; Syahrizal; Inanda, R.; Hutahean, Baskara; Handana, M.A.P
Abstract: The more widespread use of concrete and the increasing development shows that there is a greater demand for concrete so a new innovation for concrete is needed in an alternative use of basic materials. Slag cement is the result of fine grinding of steel slag which has the properties of cement which can function as an aggregate adhesive in concrete mixtures and has a fineness level that is either equal or more than type I portland cement. This research aims to compare high quality concrete made from slag cement and conventional concrete mixtures. Concrete beam samples with the size of 20 cm × 30 cm × 240 cm, with 2D10 compressive reinforcement and 3D10 tensile reinforcement. The number of samples are 6 with a variation of 3 high quality reinforced concrete with type I portland cement and 3 using slag cement. Flexture test is by analyzing the behavior of beams due to loading, crack patterns, and visual results of the beam with slag cement. From the results of the research, at the same load of 8 tons obtained a maximum deflection value of 9.52 mm on structural beams with slag cement and 13.30 mm on normal structural beams, thus structural beams with slag cement have better rigidity. The crack patterns that occur is the flextural crack patterns that occur in 1/3 of the middle span with a number of 5 cracks and a maximum crack width of 0.218 mm that occurs in structural beams with slag cement.